FACTORS INFLUENCING BRAND SWITCHING BEHAVIOR: ROLE OF VARIETY SEEKING NEED AS MODERATOR VARIABLE - FEBIASTUTI, SHEILA; NAWARINI, ALISA TRI (INDONESIAN RESEARCH SOCIETY, 2018)
The aims of research were to analyze the effect of dissatisfaction as well as characteristic ofproduct category on brand switching, to analyze the moderating role of variety seeking needon the causal relationship between dissatisfaction as well as characteristic of productcategory and brand switching, and so to analyze the direct effect of perceived price as wellas competitors? promotion on brand switching. Type of this research uses survey. Populationof this research was all customers of smartphone in Purbalingga who ever use the Samsungbrand and they switch to another brand of smartphone product which the number isuncertainty. Sampling technique of this study used interval estimate technique and theopinion by Hair et al., so it could be determined that sample size within study was 150respondents. Furthermore, technique data analysis of this study used Structural EquationModel (SEM) analysis. Based on the result of data analysis, it could be concluded thatdissatisfaction as well as characteristics of product category has a positive influence onbrand switching, need of variety seeking no moderates the influence of dissatisfaction aswell as characteristics of product category on brand switching, and perceived price toanother brand as well as competitors? promotion has a positive influence on brand switching.Refers to these conclusions, it could be implied that in order to minimize its customers?brand switching behavior, marketing manager of Samsung smartphone products needs tomake priority on marketing policy to address the customer dissatisfaction, characteristic ofproduct category, need of variety seeking, perceived price and competitors? promotionpolicies. The ways can be done by decrease the several risks are faced by Samsungsmartphone users and always to follow up the customers? complaints related to theproblems or error of the Samsung smartphone product quickly and accurately, create thespecific products of smartphone which cannot be imitated by competitors, apply the productdiversification strategy through modifying existing products or adding the new product basedon price levels and target market segmentation, make the various technological innovationsto improve the quality and usefulness of smartphone products in accordance with thechanging needs, desires and consumers? preferences, set price of Samsung smartphoneproducts that are cheaper than price of competitors? smartphone products with still maintainthe quality and benefits of Samsung smartphone products, and build the brand image of?SAMSUNG?, and always maintain and strengthen the quality of long-term marketingrelationships with its customers to keep them from being influenced by the promotionalprograms of competitors? product or brand.